Exploring the Interplay of Strengths, Positive Emotions, and Critical Thinking in Counseling Practice - Alawiyah, Tuti; Yusuf, Syamsu; Nurihsan, Juntika; Yustiana, Yusi Riska (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
This literature review explores the interplay of strengths, positive emotions, and critical thinking within the counseling practice. This literature review used a methodical approach that included a thorough search strategy in order to find and choose peer-reviewed journal articles published within the last ten years that focused on the interaction between strengths, positive emotions,and critical thinking in the counseling practice. Guided by a strengths-based approach, the review investigates how fostering positive emotions, including as appreciation, pleasure, and hope, might assist the discovery and application of client strengths.This review focused on empirical research articles, including quantitative, qualitative, and mixed-methods studies, that specifically examined the interaction between the three core constructs within the counseling context, excluding dissertations, theses, and studies focusing solely on one construct, while employing a systematic data extraction process with inter-rater reliability checks, followed by rigorous thematic analysis of the collected data.The review also explores the critical thinking abilities that are most important for enhancing the effectiveness of strengths-based therapies, including analysis, evaluation, and problem-solving.The review concludes by examining methods for incorporating critical thinking into the counseling process, such as Socratic questioning, reflective exercises, and cooperative goal planning. The results point to a synergistic interaction between critical thinking, positive emotions, and strengths that has a great deal of potential to improve client outcomes. The review does, however, also stress the significance of a well-rounded strategy that recognizes and deals with both happy and negative emotions during the counseling process.